2023
DOI: 10.3390/cancers15082198
|View full text |Cite|
|
Sign up to set email alerts
|

Androgen Receptor Activation Induces Senescence in Thyroid Cancer Cells

Abstract: Thyroid cancer (TC) is the most common endocrine malignancy, with an approximately three-fold higher incidence in women. TCGA data indicate that androgen receptor (AR) RNA is significantly downregulated in PTC. In this study, AR-expressing 8505C (anaplastic TC) (84E7) and K1 (papillary TC) cells experienced an 80% decrease in proliferation over 6 days of exposure to physiological levels of 5α-dihydrotestosterone (DHT). In 84E7, continuous AR activation resulted in G1 growth arrest, accompanied by a flattened, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 89 publications
0
6
0
Order By: Relevance
“…Local hyperandrogenism in PCOS may directly induce the cellular senescence of GCs. It has been reported that androgen receptor activation is linked to the induction of cellular senescence in some cancer cells, including thyroid ( Gupta et al , 2023 ) and prostate ( Mirochnik et al , 2012 ) cancer cells. Alternatively, hyperandrogenism may induce the senescence of GCs via the activation of ER stress.…”
Section: Discussionmentioning
confidence: 99%
“…Local hyperandrogenism in PCOS may directly induce the cellular senescence of GCs. It has been reported that androgen receptor activation is linked to the induction of cellular senescence in some cancer cells, including thyroid ( Gupta et al , 2023 ) and prostate ( Mirochnik et al , 2012 ) cancer cells. Alternatively, hyperandrogenism may induce the senescence of GCs via the activation of ER stress.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have shown that androgen-AR overexpression inhibits the migratory activity and invasive behavior of PTC cells [13], as well as the expression of programmed death receptor ligand 1 (PD-L1) in in vitro studies [8]. Activation of AR induces senescence of PTC cells [7]. Dihydrotestosterone (DHT) induces G1 arrest in androgen-responsive thyroid cancer cells [20].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have identi ed estrogen receptors, androgen receptors, prolactin receptors, and progesterone receptors expressed in PTC lesions [4,5]. It is now believed that estrogens can regulate the development of PTC through genomic or non-genomic effect [6], while androgens have been suggested to inhibit the progression of PTC in recent studies [7,8]. However, the results of these studies are mainly based on in vitro cellular experiments or animal experiments and fail to have su cient evidence for clinical studies.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have shown that androgen-AR overexpression inhibits the migratory activity and invasive behavior of PTC cells [ 13 ], as well as the expression of programmed death receptor ligand 1 (PD-L1) in in vitro studies [ 8 ]. Activation of AR induces senescence of PTC cells [ 7 ]. Dihydrotestosterone (DHT) induces G1 arrest in androgen-responsive thyroid cancer cells [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have identified estrogen receptors, androgen receptors, prolactin receptors, and progesterone receptors expressed in PTC lesions [ 4 , 5 ]. It is now believed that estrogens can regulate the development of PTC through genomic or non-genomic effect [ 6 ], while androgens have been suggested to inhibit the progression of PTC in recent studies [ 7 , 8 ]. These findings suggest that sex hormones may provide new clinical strategies for papillary thyroid cancer, such as prediction of diagnosis, endocrine therapy, and assessment of prognostic risk, as in breast cancer and prostate cancer.…”
Section: Introductionmentioning
confidence: 99%